Enhancing youth and women's financial inclusion in South Asia - Goksu Aslan (Cogent Economics & Finance, 2022)
The youthful population of South Asia, holding the majority in the subregion, will also have a great share in the future alongside the risk of being not in education, employment, or training with a persisting gender gap. This makes it important to adopt a gender-responsive policy framework for youth empowerment. This paper, after constructing a multidimensional financial inclusion index, based on a multilevel estimation framework considering the hierarchical structure of the dataset, shows evidence on how to increase financial inclusion among the South Asian youth. It furthermore provides policy recommendations considering the gendered effects. The paper finds that education level, formal employment, having a national ID, and government expenditure on education and health are important drivers of financial inclusion. The paper furthermore finds that education level becomes especially more important for those at the bottom income quintile and that government expenditure into education and health would boost the youth financial inclusion in South Asia, especially for the female youth.
Keywords: D14; G28; J16; N25; 330; financial inclusion; sustainable development goals (SDGs); youth